3rd AIAA Flow Control Conference 2006
DOI: 10.2514/6.2006-3012
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Dual Radius Circulation Control Airfoils

Abstract: I. AbstractThe goal of the work is to use multiple codes and multiple configurations to provide an assessment of the capability of RANS solvers to predict circulation control dual radius airfoil performance and also to identify key issues associated with the computational predictions of these configurations that can result in discrepancies in the predicted solutions. Solutions were obtained for the Georgia Tech Research Institute (GTRI) dual radius circulation control airfoil and the General Aviation Circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Lee-Rausch et al 2006;Shmilovich & Yadlin 2006) and over circular trailing edges (e.g. Slomski et al 2006;Swanson & Rumsey 2006).…”
Section: (B ) Separation and Controlmentioning
confidence: 99%
“…Lee-Rausch et al 2006;Shmilovich & Yadlin 2006) and over circular trailing edges (e.g. Slomski et al 2006;Swanson & Rumsey 2006).…”
Section: (B ) Separation and Controlmentioning
confidence: 99%
“…The major NASA flow solvers typify the algorithms that are most popular in the computational aerodynamics community. OVERFLOW [3] and CFL3D [4] are both based on implicit approximate factorization methods, TLNS3D [5] and CART3D [6] utilize multi-stage explicit schemes with multigrid, and FUN3D [7], although it includes a Newton-Krylov option, is usually run using either a point implicit procedure or an implicit line relaxation scheme [8]. All of these approaches are more mature than JFNK methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had found that computational meshes required much more refinement in the regions of the Coanda surface of the airfoil, along with the shear layer between the jet flow and freestream flow to more accurately capture all of the CC flow interactions. [50][51][52]54,55 With adequate refinement within these areas of complex CC flow features, the same studies saw great improvement towards matching experimental results.…”
Section: Advanced Circulation Control Airfoilsmentioning
confidence: 92%
“…9,50,51 The over prediction of lift was most commonly caused by the delay in jet separation from the Coanda surface of the airfoil. [51][52][53][54] It was found that simulations of CC airfoil geometries that employed sharp trailing edges (rather than rounded) predicted jet separation better, 51 but still over predicted lift and was not a solution for simulating the actual CC flow. The inability for these simulations to match experimental data had multiple causes, with the most significant causes being mesh refinement and turbulence modeling.…”
Section: Advanced Circulation Control Airfoilsmentioning
confidence: 99%
See 1 more Smart Citation